1971
DOI: 10.2170/jjphysiol.21.419
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Vibration Reflex in Human and Monkey Subjects

Abstract: Summary 1. Both in human subjects and monkeys, the tonic vibration reflex, TVR, was observed during vibratory stimulation of the muscle. In the latter, TVR reaches its maximum soon after vibratory application. 2. In the monkey, unitary EMG was recorded during vibratory stimulation and nonsequential interspike interval histograms were obtained. Intervals of unitary EMG were shown to occur on the principle of integer multiplication of the vibratory cyclic time. 3. A gradual increase or decrease of TVR during vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…This high degree of synchrony even at high vibration frequencies is similar to that seen in cat limb muscles (Homma et al, 1972;Matthews, 1975). The present study also confirms previous observations that vibration-induced timing of motor impulses occurs in human limb muscles (Sommer, 1941;Hufschmidt, 1958;Homma et al, 1971;Hirayama et al, 1974), but here the synchrony was found to be less pronouncedthat is, in the gross EMG recordings motor impulses were dispersed in the intervals between successive bursts. This agrees with the larger latency jitter found by Godaux et al, (1975) for the motor unit discharges in the limb muscle TVR.…”
Section: V3ibration-induc'ed Tinming Of Nmotor Likpulsfs In Jaw As Csupporting
confidence: 91%
See 1 more Smart Citation
“…This high degree of synchrony even at high vibration frequencies is similar to that seen in cat limb muscles (Homma et al, 1972;Matthews, 1975). The present study also confirms previous observations that vibration-induced timing of motor impulses occurs in human limb muscles (Sommer, 1941;Hufschmidt, 1958;Homma et al, 1971;Hirayama et al, 1974), but here the synchrony was found to be less pronouncedthat is, in the gross EMG recordings motor impulses were dispersed in the intervals between successive bursts. This agrees with the larger latency jitter found by Godaux et al, (1975) for the motor unit discharges in the limb muscle TVR.…”
Section: V3ibration-induc'ed Tinming Of Nmotor Likpulsfs In Jaw As Csupporting
confidence: 91%
“…Apart from vibration-induced positional illusions (Goodwin et al, 1972;Eklund, 1972a) and dysequilibrium reactions resulting from leg muscle vibration during standing (Eklund, 1972b), the following vibration-induced motor effects have been described: 1. A tendency for the vibration waves to affect the timing of motor unit discharges during sustained contractions, so that the gross electromyographic pattern becomes synchronized to the vibration (Sommer, 1941;Hufschmidt, 1958;Homma et al, 1971;Hirayama et al, 1974).…”
mentioning
confidence: 99%
“…This interpretation is not tenable since segmented afferent responses were also evoked from relaxed muscles without motor responses to the stretch. It has been demonstrated that when a vibrator is applied to a contracting muscle the discharges from the firing motoneurone pool tend to become monosynaptically time-locked to the vibration waves (Homma, Kanda & Watanabe, 1971;Desmedt & Godaux, 1975;Hagbarth, Hellsing & LUfstedt, 1976). Similar vibration-induced synchronization of motor discharges seems to occur transiently whenever a contracting muscle in an intact limb is passively stretched by an abrupt joint movement of sufficient speed and amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,28 In the present study, we noted, as previously, 20 that the range of vibrations eliciting the highest TVR amplitude recorded with surface electrodes was 50 -80 Hz, which is lower than that producing the maximal TVR recorded with a wire EMG electrode. 19 Further, the direct recording of afferent nerve activities in humans has shown much higher vibration frequencies to drive primary (220 Hz) or secondary endings (100 Hz). 5 The filtering effects of tissues on the surface EMG recording can probably explain such discrepancies between the vibration frequencies used to stimulate the nerve endings directly and to elicit EMG activation.…”
Section: Figurementioning
confidence: 99%